Role of Hepatic Deposited Immunoglobulin G in the Pathogenesis of Liver Damage in Systemic Lupus Erythematosus - Fang, Xiang; Zaman, Muhammad Haidar; Guo, Xuanxuan; Ding, Huimin; Xie, Changhao; Zhang, Xiaojun; Deng, Guo-Min (Frontiers in Immunology, 2018)
Onsets of hepatic disorder in systemic lupus erythematosus (SLE) patients are frequent but still the etiology and liver pathogenesis of SLE is a mystery. In this study the role of hepatic deposited immunoglobulin G (IgG) in SLE associated pathogenesis of liver damage were investigated. From retrospectively analysis of 404 lupus patient’s medical records and experimental studies on mice models, we found that liver dysfunction is common in SLE and liver damage with IgG deposition spontaneously develops in lupus-prone mice. Liver injury was reconstituted in mice by injecting lupus serum’s IgG intrahepaticaly. Liver damage was reconstituted in mice by intrahepatic injection of lupus serum IgG. The inflammation intensity of liver abrogated with IgG depletion and along with this the lupus IgG induced liver inflammation in FcγRⅢ-deficient mice were also found comparatively low, while increased in FcγRⅡb-deficient mice. Macrophages/Kupffer cells, natural killer cells and their products but not lymphocytes are required for the initiation of SLE associated liver inflammation. Blocking IgG signaling by using spleen tyrosine kinase (Syk) inhibitor suppressed the liver damage. Our findings provide the evidence of spontaneously established liver damage in lupus disease and suggest that hepatic deposited lupus IgG is an important pathological factor in the development of liver injury and that hepatic inflammation is regulated by Syk signaling pathway. And thus promote developing therapeutic strategy to control liver damage in SLE patients.